Devil's race - Avi, 1937- (New York : HarperTrophy, 1995)
Sixteen-year-old John Proud is tormented by the ghost of an evil ancestor, with his own name and his own face, who was hanged in 1854 for being a demon.
Booklist.
Bulletin (Center for Children's books).
School Library Journal.
4.4.
4.4
Young Adult
Keywords: Devil -- Fiction; Ghosts -- Fiction; Devil -- Fiction; Ghost stories